Effects of E-Wallet Adoption on Online MSMEs Performance in Indonesia - Putri, Suryani Eka; Feryanto; Burhanuddin; Purwono, Joko (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: The present study aims to analyse the causal effect of digital wallet (e-wallet) adoption on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, especially regarding monthly transaction volume and employment dynamics.Purpose: Analyse the influence of digital wallet (e-wallet) adoption on transaction frequency, non-family labour and intra-family labour of online MSMEs in Indonesia.Design/Methodology/Approach: The present study employs the Propensity Score Matching (PSM) approach to mitigate selection bias between e-wallet users and non-users. The set of covariates employed in this study encompasses educational attainment, business age, the duration of online order receipt, and digital promotional activities. The data were derived from a national survey of MSMEs, incorporating 31,724 business unit observations.Findings/Results: The findings indicate that the adoption of e-wallets is associated with a substantial augmentation in the average transaction volume, amounting to 119 transactions per month. Concurrently, there is a discernible decline in the reliance on family labour, signifying an enhancement in operational efficiency.Conclusions: The adoption of e-wallets is influenced by a number of digital factors, including the implementation of promotions through marketplaces and the duration of receiving online orders. The operational efficiency of the system is marked by a decrease in the number of internal workers. In order to encourage equitable financial inclusion, there is a necessity for the implementation of adaptive policies and comprehensive digital ecosystems.Originality/Value (State of the Art): This study makes a methodological contribution through the implementation of PSM in measuring the impact of digital financial technology adoption in developing countries. The novelty of this research lies in the integration of user behavior perspectives and empirical evaluations based on observational data, which have not been widely conducted in the context of digital MSMEs in Indonesia.Keywords:  e-wallet, MSME, propensity score matching, transaction frequency, marketplaces